Existential Despair in Kierkegaard - Beabout, Gregory (Philosophy & theology, 1991)
This paper is a study of Kierkegaard’s concept of despair. The Danish etymology of fortvivleslse is examined in order to argue that, for Kierkegaard, despair is not simply a feeling, but is more fundamentally a willed misrelation in the self.